'The pathological native' versus 'the good white girl': an analysis of race and colonialism in two Australian porn panics. Issue 1 (2nd January 2016) - Mulholland, Monique
ABSTRACT: Two examples of 'porn anxiety' have surfaced in Australia recently. The first of these is the Northern Territory Emergency Response (NTER) intervention into 73 Aboriginal communities, instigated by the Liberal Coalition Government in 2007. A key measure of the NTER is a blanket ban on pornography in these communities. The second case refers to panics about pornification, concerned about the porno-saturation of young people's cultural worlds. In both cases, a straightforward connection is made between children, pornography and harm. However, the 'problem' is constructed in very different terms. Addressing a gap in the literature, this article explores connections between race, colonialism and pornography. I unpack how 'pornography, fear and young people' is incited in each case, how the problem is differently constructed in racialized terms, and how solutions to the problem are framed. I argue that the porn panics under examination are viewed through historically persistent racialized and colonizing discourses—in the NTER case, a particular racialized child becomes the focus, in ways that entrench colonial constructions of the pathological and degenerate other. In pornification panics, while fears are couched in terms of a general unraced child, anxieties rest on securing the goodness of the white middle-class girl.